MXene-engineered lithium–sulfur batteries. Issue 40 (26th September 2019) - Xiao, Zhubing; Li, Zhonglin; Meng, Xueping; Wang, Ruihu
Abstract : The applications of MXene-based materials in cathodes, anodes and separators of lithium–sulfur batteries have been summarized, and their superiority for suppressing polysulfide shuttling and improving sulfur utilization has been demonstrated. Abstract : Lithium–sulfur (Li–S) batteries are one of the promising next-generation energy storage systems. Tremendous efforts have been devoted to developing conductive nanoarchitectures for improving sulfur utilization and cycling stability. MXenes, a family of 2D transition metal carbides, nitrides and carbonitrides, have recently captured considerable attention in energy storage and conversion. Herein, we have summarized recent advances of MXene-based materials in the cathodes, anodes and separators of Li–S batteries and highlighted the theoretical and experimental importance of high polarity and rich surface chemistry in polysulfide trapping. Their superiority for suppressing polysulfide shuttling and improving sulfur utilization has been demonstrated. We have also concluded the perspectives and challenges that need to be addressed for MXene-based Li–S batteries and some new strategies have been proposed to improve the electrochemical performance, which shed light on future development of MXene-based materials in high-energy-density Li–S batteries.